A coated lithium manganate lithium ion sieve and its preparation method and application
By covering the surface of lithium manganese lithium manganese sieve with aluminum-based adsorbent, the problems of manganese dissolution and decreased adsorption capacity during recycling of lithium manganese lithium manganese sieve are solved, and efficient lithium ion adsorption and cationic impurities removal are achieved. Improves the purity and efficiency of the lithium extraction process.
Patent Information
- Application Number
- CN202380009260.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-31
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-05-31
AI Technical Summary
The existing lithium manganate lithium ion sieve has problems such as manganese dissolution loss and decreased adsorption capacity during recycling, resulting in low lithium extraction efficiency and difficult to effectively remove cationic impurities.
The surface of lithium manganese lithium ion sieve is coated with aluminum-based adsorbent on the surface of lithium manganese oxide lithium ion sieve to form a coated lithium manganese oxide lithium ion sieve. Through the cation filtration and protection of aluminum-based adsorbent, the adsorption capacity and improvement of lithium ions are enhanced. Lithium purity.
The first adsorption capacity of lithium manganate lithium ion sieve and the adsorption capacity after recycling are significantly improved, the manganese dissolution loss is reduced, and the cationic impurities are effectively removed, which improves the purity and efficiency of the lithium extraction process.
Smart Images

Figure CN116917513B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of lithium extraction from brine, and in particular to a coated lithium manganate lithium ion sieve and a preparation method and application thereof. Background Art
[0002] Lithium is an important strategic resource and one of the most ideal materials for the development of new energy. With the increasing scarcity and depletion of mineral resources such as spodumene in recent years, the proportion of lithium extracted from salt lake brine has risen to more than 90% in the current lithium salt production in the world. Salt lake brine has a complex composition, containing a large amount of Li, Na, K, Ca, Mg, B and other ions, and the composition of brine in different geographical locations is also very different; and brine contains a large amount of alkali metals and alkaline earth metals, whose chemical properties are similar to lithium ions, which increases the difficulty of liquid lithium extraction. How to effectively separate lithium and these metals has become a global technical problem.
[0003] Through the unremitting efforts of scholars in the field, several methods for extracting liquid lithium resources have been developed, including evaporation crystallization, precipitation, solvent extraction and ion exchange adsorption. Among them, the lithium ion sieve exchange method is the most practical method for extracting lithium from dilute solutions. Lithium ion sieve is a general term for a class of adsorbents that can selectively adsorb lithium from solutions. It has a unique chemical structure. Lithium ion sieve can selectively and efficiently adsorb lithium from complex systems where multiple metal ions coexist, and the adsorption and extraction of lithium is simple, energy-saving and environmentally friendly. Therefore, lithium ion sieve technology was once considered to be the most promising solution lithium extraction technology. Among them, a certain degree of metal dissolution will occur during the desorption process of lithium manganese oxide lithium ion sieve, resulting in poor cycle performance. Therefore, since the invention of lithium ion sieve in the 1980s, it has not been used on a large scale in industrialization.
[0004] The lithium manganate lithium ion sieve in the related art generally has the problems of serious manganese dissolution and a significant decrease in adsorption capacity after multiple cycles. Therefore, it is of great significance to develop a new type of lithium ion sieve to effectively improve its adsorption capacity for lithium ions.
[0005] In view of this, the present disclosure is proposed. Summary of the invention
[0006] The purpose of the present disclosure includes providing a coated lithium manganese oxide lithium ion sieve, which can alleviate the problem of easy dissolution of manganese in the lithium ion sieve during use. At the same time, the aluminum-based adsorbent coated on the surface of the lithium manganese oxide lithium ion sieve can also play a role of selective filtration, which has a certain effect on the removal of cationic impurities in the lithium extraction process.
[0007] The purpose of the present disclosure also includes providing a method for preparing a coated lithium manganese oxide lithium ion sieve, which is simple and easy to operate, and can achieve uniform coating of the aluminum-based adsorbent on the surface of the lithium manganese oxide lithium ion sieve.
[0008] The purpose of the present disclosure also includes providing an application of a coated lithium manganate lithium ion sieve in lithium extraction from a solution.
[0009] The purpose of the present disclosure also includes providing a method for extracting lithium from salt lake brine.
[0010] In order to achieve at least one of the above-mentioned objectives of the present disclosure, the following technical solutions may be adopted:
[0011] In a first aspect, the present disclosure provides a coated lithium manganate lithium ion sieve, which comprises a lithium manganate lithium ion sieve and an aluminum-based adsorbent, wherein the molecular formula of the lithium manganate lithium ion sieve is LiMn 2 O 4 The molecular formula of the aluminum-based adsorbent is LiCl·2Al(OH) 3 ·3H 2 O, the lithium manganate lithium ion sieve is a carrier, and the aluminum-based adsorbent is coated on the surface of the lithium manganate lithium ion sieve.
[0012] In some embodiments of the present disclosure, the mass of the aluminum-based adsorbent accounts for 5%-10% of the mass of the lithium manganate lithium ion sieve.
[0013] In some embodiments of the present disclosure, the mass of the aluminum-based adsorbent accounts for 6%-9% of the mass of the lithium manganate lithium ion sieve.
[0014] In some embodiments of the present disclosure, the first adsorption capacity of the coated lithium manganate lithium ion sieve is greater than or equal to 44 mg / g, the adsorption capacity after 100 cycles is greater than or equal to 36 mg / g, and the manganese dissolution loss is less than or equal to 1.46%.
[0015] In a second aspect, the present disclosure provides a method for preparing a coated lithium manganate lithium ion sieve, comprising:
[0016] Under alkaline conditions, an aluminum-based adsorbent is coated on the surface of the lithium manganate lithium ion sieve to obtain an intermediate product;
[0017] The intermediate product is subjected to acid elution to remove lithium;
[0018] Wherein, the molecular formula of the lithium manganate lithium ion sieve is LiMn 2 O 4 The molecular formula of the aluminum-based adsorbent is LiCl·2Al(OH) 3 ·3H 2 O.
[0019] In some embodiments of the present disclosure, the step of coating the aluminum-based adsorbent on the surface of the lithium manganate lithium ion sieve under alkaline conditions comprises: mixing aluminum salt and lithium salt with water, adjusting the pH to 6.5-7.5, and obtaining a mixed solution;
[0020] The mixed solution and the lithium manganate lithium ion sieve are mixed in water, the pH of the reaction system is adjusted to 9-10, and a coprecipitation reaction is performed to obtain a precipitate as an intermediate product.
[0021] In some embodiments of the present disclosure, the mass ratio of the aluminum salt to the lithium salt is 4-6:1.
[0022] In some embodiments of the present disclosure, the aluminum salt comprises aluminum chloride.
[0023] In some embodiments of the present disclosure, the lithium salt includes lithium chloride.
[0024] In some embodiments of the present disclosure, the molar ratio of the mixed solution to the lithium manganate lithium ion sieve is 0.03-0.06:1.
[0025] In some embodiments of the present disclosure, the coprecipitation reaction is carried out at a stirring speed of 700-1000 r / min and a temperature of 70-100° C. for 4-5 h.
[0026] In some embodiments of the present disclosure, sodium hydroxide is used to adjust the pH value of the mixed solution and the reaction system.
[0027] In some embodiments of the present disclosure, when adjusting the pH value of the reaction system, the feeding rate of the sodium hydroxide is 3-5 ml / min.
[0028] In some embodiments of the present disclosure, when the mixed solution and the lithium manganate lithium ion sieve are mixed, a surfactant is also added to the system.
[0029] In some embodiments of the present disclosure, the surfactant includes at least one of an alkyl glucoside and a fatty acid glyceride.
[0030] In some embodiments of the present disclosure, the added amount of the surfactant accounts for 1-3% by volume of the base liquid in the system.
[0031] In some embodiments of the present disclosure, the acid elution of lithium includes: placing the dried intermediate product in an acid solution for immersion treatment to obtain an acidified product, and washing and drying the acidified product to obtain the coated lithium manganate lithium ion sieve.
[0032] In some embodiments of the present disclosure, the acid solution is hydrochloric acid or sulfuric acid.
[0033] In some embodiments of the present disclosure, the concentration of the acid solution is 0.25-0.5 mol / L.
[0034] In some embodiments of the present disclosure, the soaking time is 12-48 hours.
[0035] In some embodiments of the present disclosure, before the acid elution of lithium from the intermediate product, the intermediate product is further dried at 20-80° C. for 10-14 hours.
[0036] In a third aspect, the present disclosure provides an application of the coated lithium manganate lithium ion sieve prepared by the coated lithium manganate lithium ion sieve described in any one of the aforementioned embodiments or the method for preparing the coated lithium manganate lithium ion sieve described in the aforementioned embodiments in solution lithium extraction.
[0037] In a fourth aspect, the present disclosure provides an electrode for extracting lithium from salt lake brine, which comprises a coated lithium manganate lithium ion sieve prepared by the coated lithium manganate lithium ion sieve described in any one of the aforementioned embodiments or the method for preparing the coated lithium manganate lithium ion sieve described in the aforementioned embodiments.
[0038] In a fifth aspect, the present disclosure provides a method for extracting lithium from salt lake brine, which includes using an anion exchange membrane to vertically divide an electrolytic cell into a cathode chamber and an anode chamber, brine is added to the cathode chamber, and a supporting electrolyte is added to the anode chamber, the electrode for extracting lithium from salt lake brine described in any one of the preceding embodiments is placed in the brine as a cathode, an inert electrode is placed in the supporting electrolyte as an anode, and voltage is applied to the cathode and the anode to extract lithium.
[0039] Compared with the prior art, the beneficial effects of the present invention include:
[0040] The preparation method of the coated lithium manganate lithium ion sieve provided by the present disclosure adopts a coprecipitation method to coat the aluminum-based adsorbent on the surface of the lithium manganate lithium ion sieve, and the aluminum-based adsorbent on the surface of the lithium manganate lithium ion sieve can play the role of a layer of cationic impurity filter membrane, so that the lithium ion sieve has a certain automatic impurity removal process in the process of absorbing lithium ions, thereby improving the purity of lithium extraction. In addition, the aluminum-based adsorbent has strong water absorption and can play a good hydrophilic effect. Moreover, the aluminum-based adsorbent is an octahedral pore structure, which can enable brine to better penetrate into the interior of the lithium ion sieve through the aluminum-based adsorbent. Coating the aluminum-based adsorbent on the surface of the lithium ion sieve is equivalent to coating a layer of protective film on the surface of the lithium ion sieve, thereby protecting the lithium ion sieve from corrosion. The lithium ion sieve in the present disclosure can serve as a carrier during the use of the aluminum-based adsorbent, and play a certain role in fixing the aluminum-based adsorbent. In the process of lithium extraction, the aluminum-based adsorbent and the lithium manganate lithium ion sieve cooperate to play a synergistic effect, thereby significantly improving the initial adsorption capacity. The coated lithium manganate lithium ion sieve in the present disclosure can be widely used in solution lithium extraction. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 This is the SEM image of the coated lithium manganate lithium ion sieve of Example 1 of the present disclosure. DETAILED DESCRIPTION
[0043] The embodiments of the present disclosure will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. Where the manufacturers of the reagents or instruments used are not specified, they are all conventional products that can be purchased commercially.
[0044] The endpoints and any values of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0045] In a first aspect, the present disclosure provides a coated lithium manganate lithium ion sieve, which comprises a lithium manganate lithium ion sieve and an aluminum-based adsorbent, wherein the molecular formula of the lithium manganate lithium ion sieve is LiMn 2 O 4 The molecular formula of aluminum-based adsorbent is LiCl·2Al(OH) 3 ·3H 2 O, lithium manganate lithium ion sieve is used as a carrier, and an aluminum-based adsorbent is coated on the surface of the lithium manganate lithium ion sieve.
[0046] The mass of the aluminum-based adsorbent accounts for 5%-10% of the mass of the lithium manganate lithium ion sieve. In some embodiments, the mass of the aluminum-based adsorbent accounts for 6%-9% of the mass of the lithium manganate lithium ion sieve. In some embodiments, the mass of the aluminum-based adsorbent accounts for 6%-8% of the mass of the lithium manganate lithium ion sieve. The first adsorption capacity of the coated lithium manganate lithium ion sieve is greater than or equal to 44 mg / g, the adsorption capacity is greater than or equal to 36 mg / g after 100 cycles, and the manganese dissolution loss is less than or equal to 1.46%.
[0047] In a second aspect, the present disclosure provides a method for preparing a coated lithium manganate lithium ion sieve, which comprises the following steps:
[0048] S1. Prepare lithium manganate lithium ion sieve.
[0049] The lithium manganate lithium ion sieve disclosed in the present invention can be prepared independently or purchased commercially.
[0050] S2. Under alkaline conditions, an aluminum-based adsorbent is coated on the surface of the lithium manganate lithium ion sieve to obtain an intermediate product.
[0051] (1) Aluminum salt and lithium salt in a mass ratio of 4-6:1 are mixed with water, and the pH is adjusted to 6.5-7.5 to obtain a mixed solution. Optionally, the aluminum salt includes aluminum chloride; and the lithium salt includes lithium chloride.
[0052] (2) Add an appropriate amount of deionized water as a base liquid into the reactor, add the mixed solution and lithium manganate lithium ion sieve into the reactor at a molar ratio of 0.03-0.06:1, add an appropriate amount of surfactant into the system, adjust the pH of the reaction system to 9-10, and carry out a coprecipitation reaction for 4-5 hours at a stirring speed of 700-1000 r / min and a temperature of 70-100° C. to obtain a precipitate as an intermediate product.
[0053] In the present disclosure, an acid or a base is used to adjust the pH value of the mixed solution and the reaction system, and sodium hydroxide can be used to adjust the pH. When adjusting the pH of the mixed solution, the rate of adding sodium hydroxide is not limited, and it only needs to be adjusted to a preset pH. When adjusting the pH value of the reaction system, the feeding rate of sodium hydroxide is 3-5 ml / min. Since the mixed solution and the lithium manganate lithium ion sieve are undergoing a co-precipitation reaction at this time, the mixed solution is precipitated on the surface of the lithium manganate lithium ion sieve and coated on the surface of the lithium manganate lithium ion sieve, it is necessary to control the pH in real time within an appropriate range. In the present disclosure, by limiting the feeding rate of sodium hydroxide, the pH of the reaction system can be slowly adjusted, so that the reaction is milder and more complete.
[0054] In the present disclosure, the addition of surfactant can control the agglomeration state of the precipitate, so as to make the coating more uniform. The surfactant includes but is not limited to at least one of alkyl glucoside and fatty acid glyceride. The amount of surfactant added accounts for 1-3% of the volume percentage of the base liquid in the system.
[0055] S3. Post-processing.
[0056] (1) Dry the intermediate product at 20-80°C for 10-14h.
[0057] (2) Acid elution of lithium.
[0058] The dried intermediate product is placed in an acid solution for soaking to obtain an acidified product. In the present disclosure, the acid solution is hydrochloric acid or sulfuric acid, and the concentration of the acid solution is 0.25-0.5 mol / L; the acidification soaking needs to be controlled well. If the time is too short, the lithium ion leaching is insufficient, and if the leaching time is too long, it will be over-acidified, causing Mn dissolution. Therefore, the soaking time in the present disclosure is 12-48 hours.
[0059] (3) The acidified product is washed and dried to obtain a coated lithium manganate lithium ion sieve.
[0060] The acidified product is filtered, washed with deionized water, and then placed in an oven to dry at 50-70°C for 10-14 hours. The obtained powder material is the coated lithium ion sieve in the present disclosure. The inner layer of the coated lithium manganate lithium ion sieve is the lithium manganate lithium ion sieve LiMn 2 O 4 The coating layer is aluminum-based adsorbent LiCl·2Al(OH) 3 ·3H 2 O.
[0061] The preparation method of the coated lithium manganate lithium ion sieve provided in the present disclosure adopts a coprecipitation method to coat the aluminum-based adsorbent on the surface of the lithium manganate lithium ion sieve. The aluminum-based adsorbent can play the role of a layer of cationic impurity filter membrane on the surface of the lithium manganate lithium ion sieve, so that the lithium ion sieve has a certain automatic impurity removal process in the process of absorbing lithium ions, thereby improving the purity of lithium extraction. In addition, the aluminum-based adsorbent has strong water absorption and can play a good hydrophilic effect. Moreover, the aluminum-based adsorbent is an octahedral pore structure, which can enable brine to better penetrate into the interior of the lithium ion sieve through the aluminum-based adsorbent. In the present disclosure, by adding a small amount of surfactant during the coprecipitation process, the agglomeration state of the precipitate can be controlled, so that the coating is more uniform. Coating the aluminum-based adsorbent on the surface of the lithium ion sieve is equivalent to coating the surface of the lithium ion sieve with a layer of protective film, thereby protecting the lithium ion sieve from corrosion. The lithium ion sieve in the present disclosure can serve as a carrier during the use of the aluminum-based adsorbent, and play a certain role in fixing the aluminum-based adsorbent.
[0062] The coated lithium manganate lithium ion sieve provided by the present disclosure can be widely used in solution lithium extraction. In this regard, the present disclosure also provides an electrode for lithium extraction from salt lake brine, which is prepared using the above-mentioned coated lithium manganate lithium ion sieve. The specific preparation method is to directly coat the coated lithium manganate lithium ion sieve on the surface of the electrode. The present disclosure also provides a method for extracting lithium from salt lake brine, which includes using an anion exchange membrane to vertically divide the electrolytic cell into a cathode chamber and an anode chamber, brine is added to the cathode chamber, and a supporting electrolyte is added to the anode chamber. The electrode for lithium extraction from salt lake brine is placed in the brine as a cathode, and an inert electrode is placed in the supporting electrolyte as an anode, and a voltage is applied to the cathode and the anode to extract lithium.
[0063] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0064] Example 1
[0065] This embodiment provides a coated lithium manganate lithium ion sieve, wherein the mass of the aluminum-based adsorbent accounts for 5% of the mass of the lithium manganate lithium ion sieve.
[0066] The preparation method thereof comprises the following steps:
[0067] S1. Prepare lithium manganate lithium ion sieve.
[0068] (1) 0.1 g potassium permanganate was dissolved in 20 mL of 10 g / L carboxymethyl cellulose solution. After complete dissolution, the solution was transferred to a 35 mL reactor and reacted at 140 °C for 6 hours. The sample was centrifuged and dried to obtain Mn 3 O 4 ;
[0069] (2) Mn 3 O 4and lithium hydroxide in a mortar at a molar ratio of lithium to manganese of 1:2, and then calcined in a muffle furnace at a heating rate of 5°C / min and kept at 700°C for 10 hours to obtain lithium manganate;
[0070] S2. Prepare a lithium manganate lithium ion sieve with an aluminum-based adsorbent coated on the surface.
[0071] (1) Weigh 1 g of aluminum chloride and 0.2 g of lithium chloride, add them to sufficient distilled water (50 mL), stir and dissolve, add sodium hydroxide solution to adjust the pH to 7, and obtain a mixed solution;
[0072] (2) Add an appropriate amount of deionized water (100 mL) as the base liquid to the reactor at a molar ratio of 0.03:1. Take the above mixed solution and the prepared lithium ion sieve and add them to the reactor. Then add a small amount of alkyl glucoside (2 mL) to the reactor. By adjusting the feeding rate of sodium hydroxide to 4 ml / min, the pH of the solution in the reactor is controlled to be around 9 to obtain a precipitate. The reaction temperature is 80°C and the stirring speed is 800 r / min; react for 4 hours.
[0073] S3. Post-processing.
[0074] (1) The product in S2 is dried at 50° C. for 12 h to obtain a lithium manganate lithium ion sieve with an aluminum-based adsorbent coated on the surface.
[0075] (2) The coated lithium manganate lithium ion adsorbent is placed in 20 mL of 0.5 mol / L dilute hydrochloric acid and shaken at room temperature for 12 hours to complete the delithiation.
[0076] (3) The obtained product was filtered, washed, and then placed in an oven and dried at 60° C. for 12 h. The obtained powder material was the coated lithium ion sieve in this embodiment.
[0077] The coated lithium ion sieve obtained in this example was characterized by SEM. Figure 1 It can be seen that the present embodiment effectively synthesized the coated lithium manganate lithium ion sieve.
[0078] Example 2
[0079] This embodiment provides a coated lithium manganate lithium ion sieve, wherein the mass of the aluminum-based adsorbent accounts for 7% of the mass of the lithium manganate lithium ion sieve.
[0080] The preparation method thereof comprises the following steps:
[0081] S1. Prepare lithium manganate lithium ion sieve according to the method of Example 1.
[0082] S2. Prepare a lithium manganate lithium ion sieve with an aluminum-based adsorbent coated on the surface.
[0083] (1) Weigh 1 g of aluminum chloride and 0.2 g of lithium chloride, add them to 50 mL of sufficient distilled water, stir and dissolve, add sodium hydroxide solution to adjust the pH to 7, and obtain a mixed solution;
[0084] (2) Add 100 mL of deionized water as the base liquid in the reactor at a molar ratio of 0.045:1. Take the above mixed solution and the prepared lithium ion sieve and add them to the reactor. Then add a small amount of fatty acid glyceride (2 mL) to the reactor. By adjusting the feeding rate of sodium hydroxide to 4 ml / min, the pH of the solution in the reactor is controlled to be around 9 to obtain a precipitate. The reaction temperature is 80°C and the stirring speed is 800 r / min. The reaction is carried out for 4.5 hours.
[0085] S3. Post-processing.
[0086] (1) The product in S2 is dried at 50° C. for 12 h to obtain a lithium manganate lithium ion sieve with an aluminum-based adsorbent coated on the surface.
[0087] (2) The coated lithium manganate lithium ion adsorbent is placed in 20 mL of 0.5 mol / L dilute hydrochloric acid and shaken at room temperature for 24 hours to complete the delithiation.
[0088] (3) The obtained product was filtered, washed, and then placed in an oven and dried at 60° C. for 12 h. The obtained powder material was the coated lithium ion sieve in this embodiment.
[0089] Example 3
[0090] This embodiment provides a coated lithium manganate lithium ion sieve, wherein the mass of the aluminum-based adsorbent accounts for 10% of the mass of the lithium manganate lithium ion sieve.
[0091] The preparation method thereof comprises the following steps:
[0092] S1. Prepare lithium manganate lithium ion sieve according to the method of Example 1.
[0093] S2. Prepare a lithium manganate lithium ion sieve with an aluminum-based adsorbent coated on the surface.
[0094] (1) Weigh 1 g of aluminum chloride and 0.2 g of lithium chloride, add them to 50 mL of sufficient distilled water, stir and dissolve, add sodium hydroxide solution to adjust the pH to 7, and obtain a mixed solution;
[0095] (2) Add 100 mL of deionized water as the base liquid in the reactor at a molar ratio of 0.06:1. Take the above mixed solution and the prepared lithium ion sieve and add them to the reactor. Then add a small amount of alkyl glucoside (2 mL) to the reactor. The pH of the solution in the reactor is controlled at about 9 by adjusting the feeding rate of sodium hydroxide to 4 ml / min to obtain a precipitate. The reaction temperature is 80°C and the stirring speed is 800 r / min for 5 hours.
[0096] S3. Post-processing.
[0097] (1) The product in S2 is dried at 50° C. for 12 h to obtain a lithium manganate lithium ion sieve with an aluminum-based adsorbent coated on the surface.
[0098] (2) The coated lithium manganate lithium ion adsorbent is placed in 20 mL of 0.5 mol / L dilute hydrochloric acid and shaken at room temperature for 48 hours to complete the delithiation.
[0099] (3) The obtained product was filtered, washed, and then placed in an oven and dried at 60° C. for 12 h. The obtained powder material was the coated lithium ion sieve in this embodiment.
[0100] Example 4
[0101] This embodiment provides a coated lithium manganate lithium ion sieve, wherein the mass of the aluminum-based adsorbent accounts for 6% of the mass of the lithium manganate lithium ion sieve.
[0102] The preparation method thereof comprises the following steps:
[0103] S1. Prepare lithium manganate lithium ion sieve according to the method of Example 1.
[0104] S2. Prepare a lithium manganate lithium ion sieve with an aluminum-based adsorbent coated on the surface.
[0105] (1) Weigh 1.2 g of aluminum chloride and 0.2 g of lithium chloride, add them to sufficient distilled water, stir and dissolve, add sodium hydroxide solution to adjust the pH to 7, and obtain a mixed solution;
[0106] (2) Add an appropriate amount of deionized water as the base liquid to the reactor, with a molar ratio of 0.036:1. Take the above mixed solution and the prepared lithium ion sieve and add them to the reactor. Then add a small amount of alkyl glucoside (2 mL) to the reactor. By adjusting the feeding rate of sodium hydroxide to 3 ml / min, the pH of the solution in the reactor is controlled to be around 9 to obtain a precipitate. The reaction temperature is 70°C, the stirring speed is 1000 r / min, and the reaction is carried out for 4 hours.
[0107] S3. Post-processing.
[0108] (1) The product in S2 is dried at 20° C. for 14 h to obtain a lithium manganate lithium ion sieve with a surface coated with an aluminum-based adsorbent.
[0109] (2) The coated lithium manganate lithium ion adsorbent is placed in 20 mL of dilute hydrochloric acid with a concentration of 0.25 mol / L, and the lithium removal is completed after shaking at room temperature for 48 hours.
[0110] (3) The obtained product was filtered, washed, and then placed in an oven and dried at 50° C. for 14 h. The obtained powder material was the coated lithium ion sieve in this embodiment.
[0111] Example 5
[0112] This embodiment provides a coated lithium manganate lithium ion sieve, wherein the mass of the aluminum-based adsorbent accounts for 9% of the mass of the lithium manganate lithium ion sieve.
[0113] The preparation method thereof comprises the following steps:
[0114] S1. Prepare lithium manganate lithium ion sieve according to the method of Example 1.
[0115] S2. Prepare a lithium manganate lithium ion sieve with an aluminum-based adsorbent coated on the surface.
[0116] (1) Weigh 0.8 g of aluminum chloride and 0.2 g of lithium chloride, add them to sufficient distilled water, stir and dissolve, add sodium hydroxide solution to adjust the pH to 7, and obtain a mixed solution;
[0117] (2) Add an appropriate amount of deionized water as the base liquid to the reactor, with a molar ratio of 0.054:1. Take the above mixed solution and the prepared lithium ion sieve and add them to the reactor. Then add a small amount of alkyl glucoside (2 mL) to the reactor. By adjusting the feeding rate of sodium hydroxide to 5 ml / min, the pH of the solution in the reactor is controlled to be around 9 to obtain a precipitate. The reaction temperature is 100° C., the stirring speed is 700 r / min, and the reaction is carried out for 4 hours.
[0118] S3. Post-processing.
[0119] (1) The product in S2 is dried at 80° C. for 10 h to obtain a lithium manganate lithium ion sieve with an aluminum-based adsorbent coated on the surface.
[0120] (2) The coated lithium manganate lithium ion adsorbent is placed in 20 mL of 0.4 mol / L dilute hydrochloric acid and shaken at room temperature for 48 hours to complete the delithiation.
[0121] (3) The obtained product was filtered, washed, and then placed in an oven and dried at 70° C. for 10 h. The obtained powder material was the coated lithium ion sieve in this embodiment.
[0122] Comparative Example 1
[0123] The difference between this comparative example and Example 1 is that this comparative example is an uncoated lithium manganate lithium ion sieve.
[0124] S1. The lithium manganate lithium ion sieve prepared in Example 1 is placed in 20 mL of dilute hydrochloric acid with a concentration of 0.5 mol / L, and the lithium removal is completed after shaking at room temperature for 24 hours. The obtained product is filtered, washed, and placed in an oven and dried at 60° C. for 12 hours. The obtained powder material is the lithium manganate lithium ion sieve in this comparative example.
[0125] Comparative Example 2
[0126] The difference between this comparative example and Example 1 is that this comparative example uses an aluminum-based adsorbent.
[0127] S1. Weigh 1 g of aluminum chloride and 0.2 g of lithium chloride, add them to sufficient distilled water, stir and dissolve, add sodium hydroxide solution to adjust the pH to 7, and obtain a mixed solution;
[0128] S2, adding an appropriate amount of deionized water as a base liquid to the reactor, taking the above mixed solution and adding it to the reactor, and then adding a small amount of alkyl glucoside to the reactor, and adjusting the feeding rate of sodium hydroxide to 4 ml / min to control the pH of the solution in the reactor to about 9, to obtain a precipitate, the reaction temperature is 80 ° C, and the stirring speed is 800 r / min;
[0129] S3. Dry the product in S2 at 50° C. to obtain an aluminum-based adsorbent precursor.
[0130] S4, the aluminum-based adsorbent precursor was placed in 20 mL of 0.5 mol / L dilute hydrochloric acid, and the lithium removal was completed after shaking at room temperature for 12 hours. The obtained product was filtered, washed, and placed in an oven for drying at 60° C. for 12 hours. The obtained powder material was the aluminum-based adsorbent in this comparative example.
[0131] Comparative Example 3
[0132] The difference between this comparative example and Example 1 is that the carrier of this comparative example is a titanium oxide lithium ion sieve adsorbent.
[0133] S1. Weigh 1 g of aluminum chloride and 0.2 g of lithium chloride, add them to sufficient distilled water, stir and dissolve, add sodium hydroxide solution to adjust the pH to 7, and obtain a mixed solution;
[0134] S2. Add an appropriate amount of deionized water as a base liquid to the reactor at a molar ratio of 0.05:1. Take the above mixed solution and titanium oxide powder and add them to the reactor. Then add a small amount of alkyl glucoside to the reactor. Adjust the feeding rate of sodium hydroxide to 4 ml / min to control the pH of the solution in the reactor to about 9 to obtain a precipitate. The reaction temperature is 80° C. and the stirring speed is 800 r / min.
[0135] S3. Dry the product in S2 at 50° C. to obtain a titanium oxide lithium ion sieve adsorbent with an aluminum-based adsorbent coated on the surface.
[0136] S4. Place the coated titanium oxide adsorbent in 20 mL of 0.5 mol / L dilute hydrochloric acid, shake at room temperature for 12 hours to complete the delithiation, filter and wash the obtained product, and place it in an oven to dry at 60° C. for 12 hours. The obtained powder material is the coated lithium ion sieve adsorbent in this embodiment.
[0137] Comparative Example 4
[0138] The difference between this comparative example and Example 1 is that the mass of the aluminum-based adsorbent in this comparative example accounts for 15% of the mass of the lithium manganate lithium ion sieve. Among them, the preparation method of this comparative example is different from Example 1 only in step S2 (2):
[0139] Add an appropriate amount of deionized water as the base liquid in the reactor at a molar ratio of 0.09:1. Take the above mixed solution and the prepared lithium ion sieve and add them to the reactor. Then add a small amount of alkyl glucoside to the reactor. By adjusting the feeding rate of sodium hydroxide to 4 ml / min, the pH of the solution in the reactor is controlled to be around 9 to obtain a precipitate. The reaction temperature is 80°C and the stirring speed is 800 r / min.
[0140] Comparative Example 5
[0141] The difference between this comparative example and Example 1 is that the surfactant (alkyl glucoside) in Example 1 is omitted in this comparative example.
[0142] Experimental Example 1
[0143] First adsorption capacity test: initial lithium ion concentration was 165 mg / L, Mg 2+20 mL of brine with a concentration of 5 g / L and a solution pH of 12.0, 0.1 g of the lithium ion sieve prepared in Examples 1-3 and Comparative Examples 1-2 were added respectively and coated on the surface of the electrode to form an electrode for lithium extraction from salt lake brine, an anion exchange membrane was used to vertically divide the electrolytic cell into a cathode chamber and an anode chamber, brine was added to the cathode chamber, and a supporting electrolyte (50 mmol / L) was added to the anode chamber, the electrode for lithium extraction from salt lake brine was placed in the brine as a cathode, an inert electrode (activated carbon electrode) was placed in the supporting electrolyte as an anode, a voltage of 1.2 V was applied to the cathode and the anode to extract lithium, and under the conditions of 25 ° C and a reaction time of 12 h, the adsorption capacity was measured as shown in the first adsorption capacity in Table 1;
[0144] The test method of adsorption capacity after 100 cycles is consistent with the test method of initial adsorption capacity;
[0145] Mg in lithium-rich solution 2+ The concentration test method is to detect its concentration according to HJ776-2015 "Determination of 32 elements in water quality by inductively coupled plasma emission spectrometry";
[0146] The test results are shown in Table 1.
[0147]
[0148]
[0149] It can be seen from the above table that the first adsorption capacity of the coated lithium manganate lithium ion sieve provided in Examples 1-5 of the present disclosure is significantly better than that of Comparative Examples 1-5, and the adsorption capacity after 100 cycles provided in Examples 1-5 is also significantly better than that of Comparative Examples 1-5, and the Mg in the lithium-rich solution in Examples 1-5 of the present disclosure is 2+The concentration is significantly lower than that of Comparative Examples 1-5, which fully proves that the coated lithium manganate lithium ion sieve provided by the present disclosure not only has a specific adsorption effect on lithium ions, but also has a filtering effect on other impurity ions other than lithium ions, such as magnesium ions. It can be seen from Comparative Examples 1 and 2 that the coated lithium manganate lithium ion sieve provided by the present disclosure has a synergistic effect, and has a certain inhibitory effect on the dissolution of manganese metal. It can be seen from the experimental data of Comparative Example 3 that the effect of using titanium oxide lithium ion sieve as a carrier is worse than that of Example 1. The possible reason is that the lithium manganate lithium ion sieve in the present disclosure is not a conventional carrier. When the lithium manganate lithium ion sieve is not powered on, only the aluminum-based adsorbent coated on the surface absorbs lithium, and the lithium manganate material basically does not absorb lithium. When powered on, the lithium manganate lithium ion sieve and the aluminum-based adsorbent can both achieve the adsorption of lithium, which can achieve the effect of synergistic lithium absorption. It can be seen from the experimental data of Comparative Example 4 that when the proportion of the aluminum-based adsorbent in the coating layer is large, it will affect the adsorption capacity instead. It can be seen from Comparative Example 5 that when the surfactant is omitted, the precipitate will easily agglomerate during coprecipitation, resulting in uneven coating, thereby affecting the initial adsorption capacity and the manganese dissolution loss.
[0150] In summary, the preparation method of the coated lithium manganate lithium ion sieve provided in the present disclosure adopts a coprecipitation method to coat the aluminum-based adsorbent on the surface of the lithium manganate lithium ion sieve, and the aluminum-based adsorbent on the surface of the lithium manganate lithium ion sieve can play the role of a layer of cationic impurity filter membrane, so that the lithium ion sieve has a certain automatic impurity removal process in the process of absorbing lithium ions, thereby improving the purity of lithium extraction. In addition, the aluminum-based adsorbent has strong water absorption and can play a good hydrophilic effect. Moreover, the aluminum-based adsorbent is an octahedral pore structure, which can enable brine to better penetrate into the interior of the lithium ion sieve through the aluminum-based adsorbent. In the present disclosure, by adding a small amount of surfactant during the coprecipitation process, the agglomeration state of the precipitate can be controlled, so that the coating is more uniform. Coating the aluminum-based adsorbent on the surface of the lithium ion sieve is equivalent to coating the surface of the lithium ion sieve with a protective film, thereby protecting the lithium ion sieve from corrosion. The lithium ion sieve in the present disclosure can act as a carrier during the use of the aluminum-based adsorbent, and play a certain role in fixing the aluminum-based adsorbent. The aluminum-based adsorbent and the lithium manganate lithium ion sieve can cooperate to achieve a synergistic effect, thereby significantly improving the initial adsorption capacity. The coated lithium manganate lithium ion sieve disclosed in the present invention can be widely used in solution lithium extraction.
[0151] The optional implementation modes of the present disclosure are described in detail above, but the present disclosure is not limited thereto. Within the technical concept of the present disclosure, the technical solution of the present disclosure can be subjected to a variety of simple modifications, including combining various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present disclosure and belong to the protection scope of the present disclosure.
[0152] Industrial Applicability
[0153] The preparation method of the coated lithium manganate lithium ion sieve provided in the present disclosure adopts a coprecipitation method to coat the aluminum-based adsorbent on the surface of the lithium manganate lithium ion sieve. The aluminum-based adsorbent can play the role of a layer of cationic impurity filter membrane on the surface of the lithium manganate lithium ion sieve, so that the lithium ion sieve has a certain automatic impurity removal process in the process of absorbing lithium ions, thereby improving the purity of lithium extraction. In addition, the aluminum-based adsorbent has strong water absorption and can play a good hydrophilic effect. Moreover, the aluminum-based adsorbent is an octahedral pore structure, which can enable brine to better penetrate into the interior of the lithium ion sieve through the aluminum-based adsorbent. In the present disclosure, by adding a small amount of surfactant during the coprecipitation process, the agglomeration state of the precipitate can be controlled, so that the coating is more uniform. Coating the aluminum-based adsorbent on the surface of the lithium ion sieve is equivalent to coating the surface of the lithium ion sieve with a layer of protective film, thereby protecting the lithium ion sieve from corrosion. The lithium ion sieve in the present disclosure can serve as a carrier during the use of the aluminum-based adsorbent, and play a certain role in fixing the aluminum-based adsorbent. The aluminum-based adsorbent and the lithium manganate lithium ion sieve can cooperate to achieve a synergistic effect, thereby significantly improving the initial adsorption capacity. The coated lithium manganate lithium ion sieve disclosed in the present invention can be widely used in solution lithium extraction.
Claims
1. A method for preparing a coated lithium manganate lithium ion sieve, characterized in that: It includes: Under alkaline conditions, coating the surface of the lithium manganate lithium ion sieve with an aluminum-based adsorbent, wherein the mass of the aluminum-based adsorbent accounts for 5%-10% of the mass of the lithium manganate lithium ion sieve, to obtain an intermediate product; The intermediate product is subjected to acid elution to remove lithium; Wherein, the molecular formula of the lithium manganate lithium ion sieve is LiMn2O4, and the molecular formula of the aluminum-based adsorbent is LiCl·2Al(OH)3·3H2O; The step of coating the aluminum-based adsorbent on the surface of the lithium manganate lithium ion sieve under alkaline conditions comprises: mixing aluminum salt and lithium salt with water, adjusting the pH to 6.5-7.5, and obtaining a mixed solution; The mixed solution and the lithium manganate lithium ion sieve are mixed in water, the pH of the reaction system is adjusted to 9-10, and a coprecipitation reaction is performed, wherein the coprecipitation reaction is performed at a stirring speed of 700-1000 r / min and a temperature of 70-100° C. for 4-5 hours to obtain a precipitate as an intermediate product; When the mixed solution and the lithium manganate lithium ion sieve are mixed, a surfactant is added to the system, wherein the surfactant comprises at least one of alkyl glucoside and fatty acid glyceride; the added amount of the surfactant is 1-3% by volume of the base liquid in the system.
2. The method for preparing the coated lithium manganate lithium ion sieve according to claim 1, characterized in that: The mass ratio of the aluminum salt to the lithium salt is 4-6:
1.
3. The method for preparing the coated lithium manganate lithium ion sieve according to claim 1, characterized in that: The aluminum salt includes aluminum chloride.
4. The method for preparing the coated lithium manganate lithium ion sieve according to claim 1, characterized in that: The lithium salt includes lithium chloride.
5. The method for preparing the coated lithium manganate lithium ion sieve according to claim 1, characterized in that: The molar ratio of the mixed solution to the lithium manganate lithium ion sieve is 0.03-0.06:
1.
6. The method for preparing the coated lithium manganate lithium ion sieve according to claim 1, characterized in that: Sodium hydroxide is used to adjust the pH value of the mixed solution and the reaction system; when adjusting the pH value of the reaction system, the feeding rate of the sodium hydroxide is 3-5 ml / min.
7. The method for preparing the coated lithium manganate lithium ion sieve according to any one of claims 1 to 6, characterized in that: The acid elution of lithium comprises: placing the dried intermediate product in an acid solution for immersion treatment to obtain an acidified product, and washing and drying the acidified product to obtain the coated lithium manganate lithium ion sieve.
8. The method for preparing the coated lithium manganate lithium ion sieve according to claim 7, characterized in that: The acid solution is hydrochloric acid or sulfuric acid.
9. The method for preparing the coated lithium manganate lithium ion sieve according to claim 7, characterized in that: The concentration of the acid solution is 0.25-0.5 mol / L.
10. The method for preparing the coated lithium manganate lithium ion sieve according to claim 7, characterized in that: The soaking time is 12-48h.
11. The method for preparing the coated lithium manganate lithium ion sieve according to claim 1, characterized in that: Before the acid elution of lithium from the intermediate product, the method further comprises drying the intermediate product at 20-80° C. for 10-14 hours.
12. The method for preparing the coated lithium manganate lithium ion sieve according to claim 1, characterized in that: The mass of the aluminum-based adsorbent accounts for 6%-9% of the mass of the lithium manganate lithium ion sieve.
13. The method for preparing the coated lithium manganate lithium ion sieve according to claim 1, characterized in that: The first adsorption capacity of the coated lithium manganate lithium ion sieve is greater than or equal to 44 mg / g, the adsorption capacity after 100 cycles of use is greater than or equal to 36 mg / g, and the manganese dissolution loss is less than or equal to 1.46%.
14. Use of the coated lithium manganate lithium ion sieve prepared by the method for preparing the coated lithium manganate lithium ion sieve according to any one of claims 1 to 13 in lithium extraction from solution.
15. An electrode for extracting lithium from salt lake brine, characterized in that: The coated lithium manganate lithium ion sieve prepared by the method for preparing the coated lithium manganate lithium ion sieve described in any one of claims 1 to 13 is coated on the surface of an electrode substrate.
16. A method for extracting lithium from salt lake brine, characterized in that: It includes using an anion exchange membrane to vertically divide the electrolytic cell into a cathode chamber and an anode chamber, brine is added to the cathode chamber, a supporting electrolyte is added to the anode chamber, the electrode for lithium extraction from salt lake brine as claimed in claim 15 is placed in the brine as a cathode, an inert electrode is placed in the supporting electrolyte as an anode, and voltage is applied to the cathode and the anode to extract lithium.
Citation Information
Patent Citations
Composite adsorbing material for removing lithium ions in natural water and preparation method thereof
CN102872792A
Lithium ion sieve precursor with core-shell structure as well as preparation method and application of lithium ion sieve precursor
CN114887581A